L1 reading factors in extensive L2 reading-while-listening instruction. (December 2015) - Granena, Gisela; Muñoz, Carmen; Tragant, Elsa
Abstract: Extensive reading has been used as an approach to L2 instruction in foreign language contexts, where there is a need to provide rich and extensive input to learners. Previous research has shown that this type of instructional intervention is associated with improved performance in L2 reading comprehension and writing, as well as with increased positive attitudes toward L2 reading. However, not enough research has investigated the factors that mediate its effectiveness with young L2 learners. This study investigated the role of L1 reading-related factors in L2 learning under extensive reading-while-listening instruction. The findings of the study indicated a relationship between L2 learning gains in writing and positive L1 reading attitudes, a supportive reading environment at home, mother's reading interest, and parents' education level. The study concluded that extensive L2 reading-while-listening instruction allows some learners to gain additional benefits, but without disadvantaging the others. This has implications for teaching programs in the primary school context investigated, which should take learner background profiles into account when implementing this type of L2 instruction.